Resonancia magnética VS Hallazgos artroscópicos en lesiones de rodilla - Cruzado Alcántara, Mario Arturo (2020)
OBJECTIVE: To compare the findings of the reports of: Magnetic Resonance and Arthroscopy in the diagnosis of patients with knee injuries treated in the Regional Teaching Hospital of Trujillo between January 2016 - August 2018. METHODOLOGY: Retrospective, analytical and non-experimental study. The patients treated at the Teaching Regional Hospital of Trujillo between January 2016 - August 2018, with reports of magnetic resonance and affected knee arthroscopy, were considered valid diagnostic tests and the Kappa test. RESULTS: A total of 38 patients were obtained: the external meniscus was the most affected with 57.9%, followed by the internal meniscus with 50%, articular cartilage with 31.6%, synovitis with 59.9% and synovial plicae with 18.4%. Magnetic Resonance obtained a diagnostic accuracy of 81.58% in external meniscopathy, whose Kappa index between Magnetic Resonance and arthroscopy was 0.605. CONCLUSIONS: Greater pathological involvement was found in meniscal structures in both Magnetic Resonance and Arthroscopy. There is a diagnostic correlation between Magnetic Resonance and Arthroscopy in knee injuries, with greater diagnostic accuracy and "Good" Kappa agreement in the external meniscus.